Energy Intensity of Use and Socioeconomic Development in the GCC Countries: Trends and Impacts before the Pandemic - Dahan, Abdulkarim Ali; Altheeb, Rasha A.; Ali, Shrog A. (International Journal of Energy Economics and Policy, 2025)
It is anticipated that energy intensities will continue to decline, leading to a more effective distribution of energy resources that can produce wealth and a good standard of living for countries. This paper’s goal is to evaluate this trend and use a linear regression model to examine the energy intensity and how it affects growth in two of the GCC countries: Saudi Arabia and the United Arab Emirates. Initially, we examined the connection between economic growth and energy consumption, and the two countries had better results, pointing to the rise in economic activities. We then examined the connection between GDPs per capita and energy intensity of use. For the two countries, the effect of GDP per capita on intensity of use was found to be negative, indicating a reduced cost or price of transforming energy into output. Put differently, a dollar’s worth of production requires less amount of energy to be used, which will result in a more efficient use of energy. The analysis concludes that higher cost savings through more effective energy regulations will lead to more economic growth and better standard of living.